An evaluation of privatization in land development in Kelantan - 220444 Nik Hisham Nik Manshor (Skudai : Universiti Teknologi Malaysia, 2003)
Thesis (Master of Science (Land Administration and Development)) - Universiti Teknologi Malaysia, 2003